Comparative study on antibacterial activity of antibiotics, silver nanoparticles and their synergistic action on wound pathogens - PRATHIBA GNANASEKARAN; M.JANAKI VEMBU; R.SELVARAJ (International Journal of Pharma and Bio Sciences, 2017)
Antimicrobial resistance is a serious and ever growing global challenge, hence it is imperative that the antimicrobials to be used only where shown to be essential and effective. Nanosilver is the new kid on the block, generating a new wave of antimicrobial products. Carica papaya has antibacterial effects that could be useful in the treatment of chronic wound infections. In this study, antibacterial activity of antibiotics versus silver nanoparticles synthesized from unripe papaya fruit extract and their synergistic effect were determined against wound pathogens. The synthesized silver nanoparticles were confirmed by the appearance of yellowish brown colour formation at 420 nm wavelength. The inhibitory property of antibiotics, Silver nanoparticles and their synergistic activity against common wound pathogens such as Staphylococcus aureus, Pseudomonas sp, E.coli ,Klebsiella sp and Enterococci sp were studied and analyzed. The present study revealed that the synergistic effect of antibiotic and Silver nanoparticles is more efficient when compared to antibiotics or silver nanoparticles alone. Thus silver nanoparticles in combination with antibiotics can be used to treat drug resistant wound pathogens. However, a safer therapeutic regime can be established only after determining the ‘Minimum Inhibitory Concentration (MIC) and Invivo studies.